NEW EVANGELIZATION AND WORLD TRANSFORMATION: The Unique Role of Laity in Indian Society Today - Padapurackal, Cyriac (Asian Horizons, 2011)
The resurrection of Jesus Christ was the inauguration of a new humanity and it has set a new goal for history. The Church is to realize this goal of history, the transformation of humankind and creation of new world, through her revitalized and integral evangelization. This involves building up a new civilization of peace, solidarity and harmony.